HABIT+tDCS: a study protocol of a randomised controlled trial (RCT) investigating the synergistic efficacy of hand-arm bimanual intensive therapy (HABIT) plus targeted non-invasive brain stimulation to improve upper extremity function in school-age children with unilateral cerebral palsy. Issue 2 (21st February 2022) - Gordon, Andrew M; Ferre, Claudio L; Robert, Maxime T.; Chin, Karen; Brandao, Marina; Friel, Kathleen M
Abstract : Introduction: Unilateral spastic cerebral palsy (USCP) is characterised by movement deficits primarily on one body side. The best available upper extremity (UE) therapies are costly and intensive. Thus, there is an urgent need for better, more efficient and thus more accessible therapies. Transcranial direct current stimulation (tDCS) is non-invasive and may enhance physical rehabilitation approaches. The aim of this study is to determine whether tDCS targeted to the hemisphere with corticospinal tract (CST) connectivity enhances the efficacy of UE training in children with USCP. Our central hypothesis is that hand-arm bimanual intensive therapy (HABIT) combined with a tDCS montage targeting the hemisphere with CST connectivity to the impaired UE muscles will improve UE function more than HABIT plus sham stimulation. We will test this by conducting a randomised clinical trial with clinical and motor cortex physiology outcomes. Methods and analyses: 81 children, aged 6–17 years, will be randomised to receive 2 mA anodal tDCS targeted to the affected UE motor map, 2 mA cathodal tDCS to the contralesional motor cortex or sham tDCS during the first 20 min of each HABIT session (10 hours: 2 hours/day for 5 days). Primary outcomes will be Box and Blocks Test, Assisting Hand Assessment and motor cortex excitability, determined with single-pulse transcranial magnetic stimulation. Secondary outcomes include ABILHAND-Kids, Canadian Occupational Performance Measure, Cooper Stereognosis, Dimension of Mastery Questionnaire and Participation and Environment Measure–Children and Youth. All measures will be collected before, immediately and 6 months after treatment. A group × test session Analysis of Variance will test differences among groups on all measures. Ethics and dissemination: The study has been approved by the BRANY Institutional Review Board (#18-10-285-512). We will leverage our subject and family relationships to maximise dissemination and share results with the academic and patient/family advocacy groups. Trial registration number: NCT03402854 .